2006
DOI: 10.1021/jp057256h
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of Fused Tetrathiafulvalenes (TTFs) into Polythiophene Architectures:  Varying the Electroactive Dominance of the TTF Species in Hybrid Systems

Abstract: A novel polythienylenevinylene (PTV) and two new polythiophenes (PTs), featuring fused tetrathiafulvalene (TTF) units, have been prepared and characterized by ultraviolet-visible (UV-vis) and electron paramagnetic resonance (EPR) spectroelectrochemistry. All polymers undergo two sequential, reversible oxidation processes in solution. Structures in which the TTF species is directly linked to the polymer backbone (2 and 4) display redox behavior which is dictated by the fulvalene system. Once the TTF is spatiall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
78
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(84 citation statements)
references
References 73 publications
6
78
0
Order By: Relevance
“…[1][2][3] In recent years, this has 20 included the use of TTF and its derivatives as components in field-effect transistors, where several examples of materials demonstrating high mobilities have been reported. [4][5][6][7] Similarly, poly-and oligothiophenes have been shown to be viable semiconducting materials in a variety of organic electronic 25 devices, including light emitting diodes, 8,9 organic solar cells [10][11][12] and organic field effect transistors (OFETs).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…[1][2][3] In recent years, this has 20 included the use of TTF and its derivatives as components in field-effect transistors, where several examples of materials demonstrating high mobilities have been reported. [4][5][6][7] Similarly, poly-and oligothiophenes have been shown to be viable semiconducting materials in a variety of organic electronic 25 devices, including light emitting diodes, 8,9 organic solar cells [10][11][12] and organic field effect transistors (OFETs).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it has been shown that the role of the polymer/oligomer is crucial in determining whether the fulvalene unit can either dominate the electroactivity of the molecule, or participate in a hybrid redox state. 20 The electrochemical studies showed that, due to the TTF system being fused to the conjugated 40 chain through only one of the 1,3-dithiole rings, the second ring was free to act independently, providing the signature oxidation of the second dithiole moiety.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations